2010
DOI: 10.1021/ic1010677
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Single-Crystal Nuclear Resonance Vibrational Spectroscopy of [Fe(TPP)(MI)(NO)]: Quantitative Assessment of the trans Effect of NO

Abstract: This paper presents oriented single-crystal Nuclear Resonance Vibrational Spectroscopy (NRVS) data for the six-coordinate (6C) ferrous heme-nitrosyl model complex [ 57 Fe(TPP)(MI)(NO)] (1; TPP 2− = tetraphenylporphyrin dianion; MI = 1-methylimidazole). The availability of these data enables for the first time the detailed simulation of the complete NRVS data, including the porphyrin-based vibrations, of a 6C ferrous heme-nitrosyl, using our quantum chemistry centered normal coordinate analysis (QCC-NCA). Impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 93 publications
6
80
0
Order By: Relevance
“…In particular, modes of ν 53 or ν 50 character, involving stretching of the equatorial Fe-N bonds, dominate NRVS measurements on heme proteins and on model compounds and provide useful markers for the spin state of the Fe. In comparison with Fe(P), the E-symmetric modes ν 49 , ν 50 , and ν 53 in Fe(P)(Cl) mix significantly as well as shifting in frequency. In addition, Fe(P) modes involving Fe motion perpendicular to the heme plane (mainly γ 6 and γ 7 ) mix with halide translation to produce the Fe−halide stretching vibration (Fig.…”
Section: Influence Of Peripheral Substitutionmentioning
confidence: 91%
See 3 more Smart Citations
“…In particular, modes of ν 53 or ν 50 character, involving stretching of the equatorial Fe-N bonds, dominate NRVS measurements on heme proteins and on model compounds and provide useful markers for the spin state of the Fe. In comparison with Fe(P), the E-symmetric modes ν 49 , ν 50 , and ν 53 in Fe(P)(Cl) mix significantly as well as shifting in frequency. In addition, Fe(P) modes involving Fe motion perpendicular to the heme plane (mainly γ 6 and γ 7 ) mix with halide translation to produce the Fe−halide stretching vibration (Fig.…”
Section: Influence Of Peripheral Substitutionmentioning
confidence: 91%
“…The total area 0.377 accounts for the NRVS feature at 345 cm −1 (area 0.33). The NRVS peak at 391 cm −1 (area 0.17) corresponds to the DFT predicted ν 50 mode doublet of E symmetry ( Fe(P)(Cl) Fe(P) 53 (E u ) 23 (E g ) 26 (E g ) waving 50 (E u ) 49 (E u ) 22 5. Correlation between the low frequency modes of Fe(P) and modes of B 1 , E, B 2 , and A 2 C 4v symmetry classes of Fe(P)(Br).…”
Section: Assignment Of Porphine Halide Vibrationsmentioning
confidence: 91%
See 2 more Smart Citations
“…This study found the heterolytic cleavage pathway for the ðBLMÞFe III ─ H 2 O 2 complex to be thermoneutral and therefore feasible. Because ABLM is inaccessible to vibrational characterization by resonance Raman (rR) spectroscopy due to photodecay (16), we employed nuclear resonance vibrational spectroscopy (NRVS) (17)(18)(19)(20) to obtain vibrational information and define the axial ligands of Fe III BLM and ABLM, thus distinguishing between possible reaction mechanisms.…”
mentioning
confidence: 99%